ANALYSIS OF INDONESIAN ERRORS IN THE AUGUST 2023 THESIS REMOVA NEWS THROUGH TEN ONLINE NEWS SITES FROM A LINGUISTIC - Elfara Zahra Pramono; Intan Adriana Putri; Azzahra Nursamsyiah; Anisa Apriliani; Ai Siti Nurjamilah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Language acts as a means of communicating verbally and in writing. In this case, language becomes a tool for communicating emotions and thoughts through symbols that are created intentionally. Mass media is one type of media used to communicate. Mass media functions to disseminate information to readers, listeners and viewers. Online news is a form of mass media that can be accessed by the public in the current era of computers and the internet. In reality, there are still many news stories on online sites that make writing errors at a linguistic level. The aim of this research is to correct language errors at the linguistic level on online news sites regarding the deletion of theses in the August 2023 edition. This research uses a qualitative descriptive approach. The results show that from 3 news text samples taken from a total population of 10 news stories, there were five spelling errors, one error at the semantic level, two errors at the semantic level, two errors at the morphological level, and two errors at the phonological level.